DESCENTE AND KONSTATERING: TWO DIRECT EXAMINATION PROCEDURES IN CIVIL PROCEDURE LAW THAT ARE SIMILAR BUT NOT THE SAME: DESCENTE DAN KONSTATERING : DUA PROSEDUR PEMERIKSAAN SECARA LANGSUNG DALAM HUKUM ACARA PERDATA YANG SERUPA TAPI TAK SAMA - Sihotang, Paolo Omar; Soroinda, Disriani Latifah (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2025)
Descente and constatation are two legal terms in civil procedure law that often cause confusion because they are considered to be the same but are actually different. This is because both descente and constatation involve direct examination conducted outside the courtroom. Descente or on-site inspection is regulated in Article 153 HIR/180 RBg. which is an action at the evidence stage in civil proceedings carried out by a judge outside the courtroom when necessary by directly visiting an object of examination at the location where the object is located, while constatering is an act of verification at the execution stage carried out by examining the object of examination directly at its location to ensure that the object is in accordance with what is stated in the court decision. The existence of descente is very important and even mandatory to provide clarity on an event in a civil trial as stipulated in the Supreme Court Circular Letter (SEMA), namely SEMA Number 7 of 2001, SEMA Number 10 of 2020. Likewise, the existence of constatering is also no less important. The Supreme Court, through the execution guidelines issued by the Directorate General of General Courts, requires the court to conduct constatering before the eviction execution is carried out. With constatation, the court ensures that the object being executed is in accordance with the verdict and prevents errors in execution and/or execution that exceeds the verdict. Research on descente and constatation is important to clearly identify the differences between the two. Research on descente and constatering is important so that the differences between the two can be clearly identified.